Einsatz neuer Technologien in der Passagierabfertigung an Flughäfen. Ein Überblick. - Klein, Stefan; Klingler, Marico S. (Deutscher Verkehrs-Verl., 2009)
Passagierabfertigungseinrichtungen beanspruchen einen Großteil der Terminalflächen, weshalb insbesondere die Optimierung des Passagierabfertigungsprozesses im Fokus vieler Untersuchungen steht. Der Einsatz neuer Technologien ergänzt diese Bestrebungen und eröffnet neue Möglichkeiten, die bislang jedoch nur unzureichend untersucht sind.

Air traffic is a dynamic and fast growing market. Although airports and airlines are highly subject to cost pressures, investment in airport infrastructure can be a wise investment. The airport terminal is one opportunity for this type of investment. Its major function is the provision of passenger and baggage processing facilities. Use of new technologies can lead to savings in time and money for passengers, airlines and airport operators. The article shows technologies currently in use and the potential resulting benefits for passenger processing.
New technologies in passenger handling at airports.
Keywords: Verkehr; Luftverkehr; Flughafen; Leistungsfähigkeit; Terminal; Infrastruktur; Sicherheitsmaßnahme; Neue Technologie; Kosteneinsparung; Abfertigung; Passagierabfertigung; Fluggast; Kontrolle; Biometrisches Verfahren; Sicherheitskontrolle